2000
DOI: 10.1002/(sici)1099-0488(20000315)38:6<813::aid-polb1>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Partially miscible EVOH/copolyamide-6/6.9 blends: The effect of stretching on the structure

Abstract: Binary blends of random copolymers, ethylene‐vinyl‐alcohol (EVOH) consisting of 38 mol % ethylene and Copolyamide‐6/6.9 with an approximate 1 : 1 comonomer ratio, were prepared via blown‐film extrusion and uniaxial stretching. The anisotropy induced by the uniaxial deformation of the polymer blends was characterized by X‐ray diffraction and birefringence measurements. The stretched films also were investigated via oxygen permeability. The results showed a sharp decrease in the apparent crystallite size through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Incarnato et al [26] studied the relationships between composition and properties of the polyamide-6 (PA6)-ethylenevinyl-alcohol system and the results were interpreted in terms of compatibility level between both polymers. Nir et al [27] prepared binary blends of random copolymers and ethylene-vinyl-alcohol to obtain blown films and studied the barrier properties. Lu and Sue [28] prepared blown films from LDPE and linear low-density polyethylene (LLDPE) and studied the final morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Incarnato et al [26] studied the relationships between composition and properties of the polyamide-6 (PA6)-ethylenevinyl-alcohol system and the results were interpreted in terms of compatibility level between both polymers. Nir et al [27] prepared binary blends of random copolymers and ethylene-vinyl-alcohol to obtain blown films and studied the barrier properties. Lu and Sue [28] prepared blown films from LDPE and linear low-density polyethylene (LLDPE) and studied the final morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Cerreda et al have shown that the composition and the thermal history of EVOH film also influence the crystalline structure. Therefore, it would be better to estimate the degree of crystallinity from the X-ray diffraction measurements by calculating the ratio of the crystalline peak area to the total area . In our case, the influence of plasma treatment on crystallinity rate can be discussed on the basis of the quantity of Δ H m – Δ H c calculated from TMDSC results (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it would be better to estimate the degree of crystallinity from the X-ray diffraction measurements by calculating the ratio of the crystalline peak area to the total area. 43 In our case, the influence of plasma treatment on crystallinity rate can be discussed on the basis of the quantity of ΔH m − ΔH c calculated from TMDSC results (Table 4). In general, from TMDSC data and taking into account the error of measurements, one can conclude that the cold plasma treatment has practically no influence on the thermal properties of EVOH films.…”
Section: Atomic Force Microscopy (Afm)mentioning
confidence: 99%
“…Blend technology has been widely exploited to improve the barrier properties of polymers. [ 13–19 ] A representative example is a polyolefin and EVOH blend, where the poor oxygen barrier properties of polyolefin were improved by the addition of EVOH. [ 17–19 ] While PK does have moderately high oxygen barrier properties, its use in packaging products has been limited owing to the demand for oxygen transmission rates (OTR) of <1.0 cc m −2 day −1 atm −1 .…”
Section: Introductionmentioning
confidence: 99%